[177Lu]Lu-DOTA-TATE and [131I]MIBG Phenotypic Imaging-Based Therapy in Metastatic/Inoperable Pheochromocytomas and Paragangliomas: Comparative Results in a Single Center - Prado-Wohlwend, Stefan; del Olmo-García, María Isabel; Bello-Arques, Pilar; Merino-Torres, Juan Francisco (Frontiers in Endocrinology, 2022)
Purpose The aim of the study is to assess phenotypic imaging patterns and the response to treatment with [177Lu]Lu-DOTA-TATE and/or [131I]MIBG in paragangliomas (PGLs) and pheochromocytomas (PHEOs), globally and according to the primary location. Methods This is a 17-patient retrospective observational study, with 9 cases treated with [177Lu]Lu-DOTA-TATE and 8 with [131I]MIBG (37 total treatments). Functional imaging scans and treatment responses were studied in order to choose the best therapeutic option and to define the progression-free survival (PFS) and disease control rate (DCR) according to treatment modality and primary location. Results All patients were studied with phenotypic nuclear medicine images. Twelve of 17 patients were tested with both [123I]MIBG and somatostatin receptor images, and 6/12 showed appropriate expression of both targets to treatment in the phenotypic images. The rest of the patients were tested with one of the image modalities or only showed suitable uptake of a single radiotracer and were treated with the corresponding therapeutic option. [177Lu]Lu-DOTA-TATE PFS was 29 months with a DCR of 88.8%. [131I]MIBG PFS was 18.5 months with a 62.5% DCR. According to the primary location, the best PFS was in PHEOs treated with [177Lu]Lu-DOTA-TATE. Although the series are small due to the low disease prevalence and do not allow to yield statistically significant differences, this first study comparing [177Lu]Lu-DOTA-TATE and [131I]MIBG displays a trend to an overall longer PFS with [177Lu]Lu-DOTA-TATE, especially in the adrenal primary location. When both radionuclide targets are expressed, the patients’ comorbidity and treatment effectiveness should be valued together with the intensity uptake in the phenotypic image in order to choose the best therapeutic option. These preliminary retrospective results reinforce the need for a prospective, multicentric trial to be confirmed.